A Science-Based Modification of The Boi-Boian Game To Stimulate Science Process Skills In Early Childhood - Rizka Maulia; Euis Kurniati (Eduvest - Journal of Universal Studies, 2022)
This study aims to analyze the implementation of a science-based Boi-boian game modification in stimulating Science Process Skills (SPS) in early childhood. This learning innovation is expected to restore children's mental health due to not inadequate play activities. In addition, this modification is also expected to solve lost learning due to lack of stimulation during online learning. The method used in this research is qualitative with the research subject, namely a group of eight children in a kindergarten in Parongpong, West Java. Data collection was carried out by audiovisual records and observation. Furthermore, the results of the data were analyzed using six steps, including data collection, data organization, reading the entire data, data coding, data interrelation, and interpretation of meaning. The results show that the science-based modification of the Boi-boian game can invite children to explore, observe, and solve problems. These activities stimulate the ability to predict, ask questions, observe, classify, differentiate, measure, record, and communicate. In practice, learning development can also stimulate the emergence of critical and creative thinking skills in children. The emergence of various SPS is supported by two factors, namely the four principles of learning science in early childhood and classroom management.